Epidemiological study and variation analysis of the porcine kobuvirus 3D gene in Sichuan province, China - Liu, Pengjuan (Virol Sin, 2015)
[Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s12250-015-3632-1 and is accessible for authorized users.